Relationship between special fitness test score and anaerobic lower limb power among female Japanese judokas - Okawa, M.; Ide, Y.; Okada, Y.; Sakurai, T. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: The judo is performed by the Olympic Games and the world championship. The purpose of this study was examined the relationship between Special Judo Fitness Test (SJFT) index and lower limb power in female Japanese judokas. Methods: Seventeen female judokas (mean age 20.9±0.8 yrs, mean height 162.9±5.6 cm, and mean body mass 70.3±12.9 kg) performed the SJFT, which comprised three periods (1st =15 seconds, 2nd and 3rd=30 seconds interspersed with 10 seconds rest intervals) test for judo players. During this test, one athlete threw two others positioned 6 m from each other using the ippon-seoi-nage (one arm back carry throw) technique, created and described by Sterkowicz (1995). The following variables were quantified: throws performed during series 1st, 2nd, and 3rd; total number of throws. Anaerobic lower limb power was measured using 30 seconds Wingate Anaerobic Test (WAnT) carried out by ergometric cycle. Data was analyzed with Peason`s correlation test between the number of throw by SJFT and lower limb power, and used repeated measures ANOVA. Significance level was adopted as =.05 and =.30 (effect size [r] is used as the evaluation by Cohen [1988] were used in analyses [Small: .10, Medium: .30, and Large: .50]). Results & Discussion: Mean values (±SD [lower 95%CI, upper 95%CI]) the number of SJFT throws were 1st: 5.3±0.7, 2nd: 9.8±0.9, 3rd: 9.9±0.8 (p<.001, generalized eta squared=.885 [.802, .934], generalized omega squared=.878 [.791, .930], and probability of replication=1.00) (Olejnik and Algina [2003]), and total throws was 24.9±2.2. The values of mean power and peak power were 436.8±83.3 watts and 567.3±117.4 watts. It was negative correlation between the number of total throw by SJFT and lower limb power (mean power: r=-.554 [-.817, -.101], p=.021, and power=.67. And peak power: r=-.496 [-.789, -.020], p=.043, and power=.55). Szmuchrowski (2013) reported no significance correlation between the SJFT and WAnT results, which was supported in this study. On the other hand, Franchini et al (2009) who found a correlation between the SJFT and WAnT results. It is necessary to consider whether this SJFT is effective for female judo players.